Dynamics of former ice lobes of the southernmost Patagonian Ice Sheet based on a glacial landsystems approach. (16th September 2016) - Darvill, Christopher M.; Stokes, Chris R.; Bentley, Michael J.; Evans, David J. A.; Lovell, Harold
ABSTRACT: Reconstructions of former ice masses from glacial geomorphology help to constrain the nature and timing of glaciation in relation to climatic forcing. This paper presents a new reconstruction of the glacial history of five ice lobes in southernmost South America: the Bahía Inútil − San Sebastián, Magellan, Otway, Skyring and Río Gallegos ice lobes. We use previous geomorphological mapping of glacial landforms to reconstruct former glacial limits and proglacial lakes, demarcate flow‐sets from the distribution of glacial lineations, and evaluate glacial landsystem signatures and their palaeoglaciological implications. Evidence suggests that the ice lobes predominantly reflect active temperate glacial landsystems, which may have switched to polythermal systems when periods of cold‐based ice developed ephemerally. This complex landsystem signature implies that the ice lobes were sensitive to regional climate variability, with active re‐advances during overall retreat of the ice margins. There is also evidence for periods of fast ice flow and possible surge‐like activity in the region, followed by the rapid retreat or even collapse of some of the ice lobes in association with proglacial lakes. Constraining our new reconstruction with published chronological information suggests that at least some of the ice lobes advanced before the global Last Glacial Maximum (gLGM: ca. 26.5–19 ka) during the last glacial cycle. Our new reconstruction demonstrates a more complex picture of ice dynamics than has previously been portrayed, and one in which the advance and retreat of the ice lobes was likely to have been primarily driven by changes in climate. As such, ice advances before the gLGM in the southernmost part of the Patagonian Ice Sheet are likely to indicate a wider climatic forcing at this time.